A Bibliometric Analysis on Mental Health Research Over the Past Two Decades: Bibliometric Trends in Mental Health Research - Ranta, Randhir Singh; Sharma, Tanuj; Sharma, Aditi (Journal of Medical Health Research and Psychiatry, 2025)
The research examined mental health publications through a comprehensive bibliometric analysis from 2000 to 2024, encompassing 483 documents published in 279 outlets that had an annual growth rate of 9.5%. The research explored publication trends; leading journals; key authors; key affiliations; collaboration networks of authors, institutions and countries; co-occurrence networks and identified major trending topics and themes. Research has shown that mental health article output experienced a significant growth after 2018 because of new policies and worldwide mental health concerns. Three prominent journals, Psychiatric Services, BMC Psychiatry and The Lancet lead the field because they demonstrate the critical nature of psychiatric and public health research. This analysis highlighted the leading researchers as well as prominent scholarly works while demonstrating that Harvard University and the University of Toronto made significant research contributions. The co-occurrence analysis and thematic map revealed four principal subjects: mental health services, depression, public health policy research and socioeconomic influences. The research investigated international research collaborations where the USA had a leading position in global collaboration. The effect of COVID-19 on mental health and cognitive behavioural therapy were the emerging topics in this field of research. The findings provide essential information about ongoing research trends as well as about influential publications and collaborations that direct future studies.